Different Kinematics of Knees with Varus and Valgus Deformities - Baier, C.; Benditz, A.; Koeck, F.; Keshmiri, A.; Grifka, J.; Maderbacher, G. (The Journal of Knee Surgery, 2018)
Few data exist of kinematics of knees with varus and valgus deformities combined with osteoarthritis. The purpose of this study was to reveal different (1) tibiofemoral kinematics, (2) medial and lateral gaps, and (3) condylar liftoff of osteoarthritic knees with either varus or valgus deformity before and after total knee arthroplasty (TKA). For this purpose, 40 patients for TKA were included in this study, 23 knees with varus deformity and 17 knees with valgus deformity. All patients underwent computer navigation, and kinematics was assessed before making any cuts or releases and after implantation. Osteoarthritic knees with valgus deformity showed a significant difference in tibia rotation relative to the femur with flexion before and after TKA, whereas knees with varus deformity did not. Knees with a valgus deformity showed femoral external rotation in extension and femoral internal rotation in flexion, whereas knees with a varus deformity revealed femoral internal rotation in extension and femoral external rotation in flexion. In both groups, gaps increased after TKA. Condylar liftoff was not observed in the varus deformity group after TKA. In the valgus deformity group, condylar liftoff was detected after TKA at knee flexion of 50 degrees and more. This study revealed significant differences in tibiofemoral kinematics between osteoarthritic knees with a varus or valgus deformity before and after TKA. Valgus deformities showed a paradoxic movement pattern. These in vivo intraoperative results need to be confirmed using fluoroscopic or radiographic three-dimensional matching before and after TKA.
Keywords: varus deformity; valgus deformity; knee kinematics